VD_FINDINFO HC / 2013 / 649 vom 14. August 2013 - VD Tribunal cantonal (2013)
DROIT DE LA FONCTION PUBLIQUE, ENSEIGNANT, TRAVAIL À TEMPS PARTIEL, DROIT PRIVÉ | 49 CO, 308 al. 1 let. a CPC (CH), 308 al. 2 CPC (CH), 310 CPC (CH), 317 al. 1 CPC (CH)